Effect of Artery Diameter and Velocity and Vein Diameter on Upper Limb Arteriovenous Fistula Outcomes - Morwan Bahi (The Scientific World Journal)
Objective. Haemodialysis is an important tool for end-stage renal disease (ESRD) patients to correct electrolyte disturbance and improve life quality. This requires a method of long-term vascular access. For many ESRD patients, arteriovenous fistula (AVF) formation is the optimal method of access. AVF success and patency are critical to allow access for haemodialysis. Failure to mature and thrombosis are key factors involved in AVF failure. Our aim is to report outcomes from a single-centre, retrospective study investigating the association between artery and vein measurements as well as intraoperative heparin use on autogenous upper limb AVF outcomes. Methods. This retrospective study analyses the influence of artery and vein diameter on AVF outcomes over a 12-month period, from 1 January 2019 through 31 December 2019. The key endpoint was AVF patency and functionality at 6 weeks postoperatively. Results. During our study period, 66 autogenous upper limb AVFs were formed in our tertiary vascular centre. This included 44 radiocephalic, 11 brachiocephalic, and 11 brachiobasilic AVFs. We report an association between minimum vein diameter >2.0 mm and arterial diameter >2.0 mm and AVF success and functionality. Our data did not support intraoperative heparin use as a measure to improve AVF success. Conclusion. This study suggests a statistically significant association between vein and artery diameter (>2.0 mm) with improved AVF patency at 6 weeks postoperatively. We did not observe benefit from intraoperative heparin use.